Bilateral coronary artery-pulmonary artery fistulas in mitral stenosis: A case report - Uysal, Ayhan; Burma, Oktay; Akbulut, Mehmet (My University, 2013)
Coronary arteriovenous fistulas, being a rare entity of congenital abnormalities of the coronary arteries, are usually diagnosed incidentally during coronary angiography. These fistulas may result in a substantial level of cardiac morbidity and mortality, leading to angina, syncope, congestive heart failure, myocardial infarction, endocarditis, pulmonary embolism and sudden death. In this article, we present, a 48-year-old female case with coronary arteriovenous fistulas originating from both the right coronary and left anterior descending coronary artery and draining to the main pulmonary artery which were diagnosed during cardiac catheterization and coronary angiography accompanied by rheumatic mitral stenosis in the light of the literature.
Mitral stenozda iki tarafli koroner arter-pulmoner arter fistülleri: Olgu sunumu
Keywords: Arteriovenous; Coronary; Fistula; Mitral